2009
DOI: 10.1084/jem.20081571
|View full text |Cite
|
Sign up to set email alerts
|

The induction of antibody production by IL-6 is indirectly mediated by IL-21 produced by CD4+ T cells

Abstract: Interleukin (IL) 6 is a proinfl ammtory cytokine produced by antigen-presenting cells and nonhematopoietic cells in response to external stimuli. It was initially identifi ed as a B cell growth factor and inducer of plasma cell differentiation in vitro and plays an important role in antibody production and class switching in vivo. However, it is not clear whether IL-6 directly affects B cells or acts through other mechanisms. We show that IL-6 is suffi cient and necessary to induce IL-21 production by naive an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

26
338
1
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 369 publications
(367 citation statements)
references
References 42 publications
26
338
1
2
Order By: Relevance
“…4) suggest that CD11b 1 Gr-1 1 inflammatory myeloid cells might regulate the generation of CD4 1 Tfh-like cells. Furthermore, CD11b 1 Gr-1 1 inflammatory myeloid cells produced IL-6, one candidate cytokine for Tfh-cell differentiation [37,38], and also expressed ICOSL and PD-L1. However, the requirement of IL-6 for Tfh cell development in vivo is still controversial [38], and IL-6 might influence B-cell activation T-cell-independent manner.…”
Section: Discussionmentioning
confidence: 99%
“…4) suggest that CD11b 1 Gr-1 1 inflammatory myeloid cells might regulate the generation of CD4 1 Tfh-like cells. Furthermore, CD11b 1 Gr-1 1 inflammatory myeloid cells produced IL-6, one candidate cytokine for Tfh-cell differentiation [37,38], and also expressed ICOSL and PD-L1. However, the requirement of IL-6 for Tfh cell development in vivo is still controversial [38], and IL-6 might influence B-cell activation T-cell-independent manner.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, IL-6 is a immunomodulatory cytokine that was systemically high in the serum. It controls plasma B-cell differentiation, and it influences also T helper cell cytokine production through Stat3-dependent signaling (1,(25)(26)(27). Stat3 isoforms are known to cooperate with c-Jun or JunD proteins specifically (33).…”
Section: Discussionmentioning
confidence: 99%
“…S4 I and E), indicating that G-CSF is not responsible for the autoimmune phenotype. IL-6-Jak1-Stat3 activation promotes plasma B-cell differentiation either directly (26) or indirectly through CD4 ϩ T helper cells (27). To investigate the role of lymphocytes in the development of local and systemic autoimmune alterations, JunB ⌬ep mice were crossed with Rag2 Ϫ/Ϫ mice.…”
Section: Sle Phenotype By Junb ⌬Ep and Rescue By Il-6mentioning
confidence: 99%
“…In vitro studies in IL-6-knockout mice have shown a marked reduction in B cell immune responses (7), particularly reductions in the levels of IgG1, IgG2a, and IgG3 upon immunization with a T cell-dependent antigen (8), suggesting that IL-6 is central for the induction and/or maintenance of plasma cells that produce these immunoglobulin subclasses. A recent study showed that antibody production is indirectly promoted by B cell helper capabilities of CD4ϩ T cells through increased IL-21 production upon IL-6 stimulation (9).…”
mentioning
confidence: 99%